The true life of Habibie : cerita di balik kesuksesan - Makka, A. Makmur, 1945- ([Cinere, Depok] : Pustaka Ilman, 2008)
Biography of B.J. Habibie, former president of Republic of Indonesia.
Includes bibliographical references.
In Indonesian.
Keywords: Habibie, B. J. -- 1936-; Presidents -- Indonesia -- Biography; Indonesia -- Politics and government -- 1998-